Money, Output, and the Nominal National Debt - Champ, Bruce; Freeman, Scott (American Economic Review, 1990)
This paper presents a model of finitely lived rational agents in which unanticipated innovations in the stock of fiat money affect real variables. An unanticipated inflation reduces the real value of the nominally denominated national debt, thereby reducing the crowding-out of capital and/or the tax burden. Both effects stimulate increased investment in capital, which leads to an increase in real output and wages in the following periods. In contrast with price-surprise models, these real effects occur even if the monetary innovation is instantly and perfectly observed by agents. Copyright 1990 by American Economic Association.